CD4 T-Cell-Independent Antibody Response Reduces Enterovirus 71 Lethality in Mice by Decreasing Tissue Viral Loads - Li-Chiu Wang; Chia-Min Kao; Pin Ling; Ih-Jen Su; Tung-Miao Chang; Shun-Hua Chen (Clinical and Developmental Immunology)
Enterovirus 71 (EV71) has induced fatal encephalitis in hundreds of thousands of infants and young children in the Asia-Pacific region since the past decade. Lymphocyte and antibody responses have been suspected to aggravate EV71-induced neurological symptoms, so anti-inflammatory agents have been used to treat patients with neurological symptoms. In the present study, we found that mice deficient in CD4+ T cells were resistant to EV71 infection as wild-type mice, whereas mice deficient in B cells were highly susceptible to viral infection. Compensation of CD4 T-cell function by other immune cells was not likely, because wild-type mice depleted of CD4+ T cells were also resistant to viral infection. Infected CD4 T-cell-deficient mice produced virus-specific neutralizing antibodies, IgM and IgG. Moreover, adoptive transfer of the virus-specific antibody produced by infected CD4 T-cell-deficient mice protected B-cell-deficient mice from infection by reducing tissue viral loads. Collectively, our results show that the CD4 T-cell-independent antibody response promotes the survival of EV71-infected mice and suggest great potential for the use of vaccines and neutralizing antibodies to reduce fatal symptoms in patients.